Activation Of Glycoprotein Hormone Receptors : Role Of Different Receptor Domains In Hormone Binding And Signaling - Majumdar, Ritankar (2014)
The glycoprotein hormones, Luteinizing Hormone (LH), human Chorionic Gonadotropin (hCG), Follicle Stimulating Hormone (FSH) and Thyroid Stimulating Hormone (TSH) are heterodimeric proteins with an identical α-subunit associated non-covalently with the hormone specific β-subunit and play important roles in reproduction and overall physiology of the organism [1]. The receptors of these hormones belong to the family of G-protein coupled receptors (GPCR) and have a large extracellular domain (ECD) comprising of 9-10 leucine rich repeats (LRR) followed by a flexible hinge region, a seven helical transmembrane domain (TMD) and a C terminal cytoplasmic tail [2]. Despite significant sequence and structural homologies observed between the ECDs of the receptors and the specific β-subunits of the hormones, the hormone-receptor pairs exhibit exquisite specificity with very low cross-reactivity with other members of the family. The TSH receptor (TSHR) is an especially interesting member of this family as it not only recognizes is cognate ligand, i.e. TSH, but also binds to the non-cognate ligands such as autoantibodies. TSHR autoantibodies come in different flavors; inhibitory antibodies that compete with the hormone for receptor binding and block its action, stimulatory antibodies that activate the receptor in a hormone independent manner and neutral antibodies that bind to the receptor but do not directly influence its functions. The inhibitory autoantibodies cause hypothyroidism and are responsible for Hashimoto’s Thyroiditis, whereas the stimulatory autoantibodies cause Graves’ thyrotoxicosis characterized by hyperthyroid condition [3]. The exact epitopes of these autoantibodies are not well delineated although it has been hypothesized that the blocking type- and the stimulatory type- autoantibodies have predominant epitopes in the TSHR ECD that overlap with hormone binding regions [4]. Insights into the mode of hormone or autoantibody binding to the receptor was primarily derived from the crystal structure of FSHR leucine rich repeat domain (LRRD) bound to single chain analog of FSH, and the crystal structures of TSHR LRRD bound to the stimulatory type human monoclonal antibody M22 [5] and the inhibitory type- monoclonal antibody K1-70 [6]. Both these crystal structures propose LRRDs as the primary ligand binding site which interacts with the hormone through its determinant loop in a hand-clasp fashion [7] while the autoantibodies mimics the hormone binding to a large extent [8] . These structures, while providing detailed understanding of the molecular interactions of the LRRs with the hormone, shed little light on the mechanism by which the signal generated at the LRRD are transduced to the downstream effector regions at the distally situated TMD. Hence, while one understands the ligand binding to a large extent, the activation process is not well understood, one of the central objective of the present study. Ligand-receptor interactions are typically studied by perturbing ligand/receptor structure by mutagenesis or by mapping conformational changes by biophysical or computational approaches. In addition to the above-mentioned approaches, the present work also uses highly specific antibodies against different domains of the receptor as molecular probes due to the ability of antibodies to distinguish between conformations likely to arise during the activation process. Use of antibodies to understand the receptor activation process is especially apt for TSHR due to the presence of physiologically relevant TSHR autoantibodies and their ability to influence hormone binding and receptor activation [9, 10]. Chapter 2 attempts to provide a comparison between the interactions of the hormone and the autoantibodies with TSHR. For this purpose, two assays were developed for identification of TSHR autoantibodies in the sera of patients suffering from autoimmune thyroid diseases (AITD), the first assay is based on the ability of TSHR autoantibodies to compete for radiolabeled hormone (The TSH binding inhibition (TBI), assay) and the second based on the capability of stimulatory antibody to produce cAMP in cells expressing TSHR (TSHR stimulatory immunoglobin (TSI) assay). A stable cell line expressing TSHR capable of recognizing both TSH and TSHR autoantibodies was thus created and used for prospective and retrospective analysis of AITD patients. Based on the TBI and TSI profiles of IgGs, purified from AITD patient's sera, it was recognized that TSHR stimulatory and TSH binding inhibitory effects of these antibodies correlated well, indicating overlap between hormone binding and IgG binding epitopes. It was also recognized that stimulatory IgGs are not affected by negative regulatory mechanism that governs TSH secretion substantiating the persistence of these antibodies in circulation. Kinetics of cAMP production by Graves’ stimulatory IgG was found to be fundamentally distinct, where the autoantibodies displayed pronounce hysteresis during the onset of the activation process when compared to the hormone. This could possibly be explained by the oligoclonality of the autoantibody population, a different mechanism of receptor activation or dissimilarity in autoantibody and hormone epitopes. To gain additional insights into the epitopes of TSHR autoantibodies and the regions that might be critical in the activation process, different overlapping fragments encompassing the entire TSH receptor ECD were cloned, expressed in E.coli as GST fusion proteins and purified: 1] the first three LRRs (TLRR 1-3, amino acid (aa) 21-127), 2] the first six LRRs (TLRR 1-6, aa 21-200), 3] the putative major hormone binding domain (TLRR 4-6, aa 128-200), and 4] the hinge region of TSH receptor along with LRR 7 to 9, (TLRR 7-HinR, aa 201-413). The receptor fragment TLRR 7-HinR was further subdivided into LRR 7-9 (TLRR 7-9, aa 201-161) and the hinge region (TSHR HinR, aa 261-413), expressed as N-terminal His-Tagged protein and purified using IMAC chromatography. Simultaneously, the full-length TSHR ECD was cloned, expressed and purified using the Pichia pastoris expression system. ELISA or immunoblot analysis of autoantibodies with the TSHR exodomain fragments suggested that Graves’ stimulatory antibody epitopes were distributed throughout the ECD with LRR 4-9 being the predominant site of binding. Interestingly, experiments involving neutralization of Graves’ IgG stimulated cAMP response by different receptor fragment indicated that fragments corresponding to the TSHR hinge region were better inhibitors of autoantibody stimulated receptor response than corresponding LRR fragments, suggesting that the hinge region might be an important component of the receptor activation process. This was in contrast to prevalent beliefs that considered the hinge region to be an inert linker connecting the LRRs to the TMD, a structural entity without any known functional significance. Mutagenesis in TSHR hinge region and agonistic antibodies against FSHR and LHR hinge regions, reported by the laboratory, recognized the importance of the hinge regions as critical for receptor activation and may not simply be a scaffold [11-13]. Unfortunately, the mechanism by which the hinge region regulates binding or response or both have not been well understood partially due to unavailability of structural information about this region. In addition poor sequence similarity within the GpHR family and within proteins of known structure, make this region difficult to model structurally. In chapter 3, effort is made to model the hinge regions of the three GpHR based on the knowledge driven and Ab initio protocols. An assembled structure comprising of the LRR domain (derived from the known structures of FSHR and TSHR LRR domains) and the modeled hinge region and transmembrane domain presents interesting differences between the three receptors, especially in the manner the hormone bound LRRD is oriented towards the TMD. These models also suggested that the α-subunit interactions in these three receptors are fundamentally different and this was verified by investigating the effects of two α-subunit specific MAbs C10/2A6 on hCG-LHR and hTSH-TSHR interactions. These two α-subunit MAbs had inverse effects on binding of hormone to the receptor. MAb C10 inhibited TSH binding to TSHR but not that of hCG, whereas MAb 2A6 inhibited binding of hCG to LHR but not of hTSH. Investigation into the accessibility of their epitopes in a preformed hormone receptor complex indicated that the α-subunit may become buried or undergo conformational change during the activation process and interaction may be different for LHR and TSHR. Fundamental differences in TSHR and LHR were further investigated in the next chapter (Chapter 4), especially with regards to the ligand independent receptor activation. Polyclonal antibodies were developed against LRR 1-6, TLRR 7-HinR and the TSHR HinR receptor fragments. The LRR 1-6 antibodies were potent inhibitor of receptor binding as well as response, similar to that observed with antibodies against the corresponding regions of LHR. Interestingly, the antibodies against the hinge region of TSHR were unable to inhibit hTSH binding, but were effective inhibitors of cAMP production suggesting that this region may be involved in a later stage of a multi-step activation process. This was also verified by studying the mechanism of inhibition of receptor response and their effect on ligand-receptor association and dissociation kinetics. Hinge region-specific antibodies immunopurified from TLRR 7-HinR antibodies behaved akin to those of the pure hinge region antibodies providing independent validation of the above results. This result was, however, in contrast to those observed with a similar antibody against LHR hinge region. As compared to the TSHR antibody, the LHR antibody inhibited both hormone binding and response. In addition, this antibody could dissociate a preformed hormone-receptor complex which was not observed for TSHR hinge region antibodies. Although unable to dissociate preformed hormone-receptor complex by itself, the TSHR HinR antibodies augmented hormone induced dissociation of the hormone-receptor complex suggesting that this region may be involved in modulation of negative cooperativity associated with TSHR. Molecular dissection of the role of hinge region of TSHR was further carried out by using monoclonal antibodies against LRR 1-3 (MAb 413.1.F7), LRR 7-9 (MAb 311.87), TSHR hinge region (MAb 311.62 and MAb PD1.37). MAb 311.62 which identifies the LRR/Cb-2 junction (aa 265-275), increased the affinity of TSHR for the hormone while concomitantly decreasing its efficacy, whereas MAb 311.87 recognizing LRR 7-9 (aa 201-259) acted as a non-competitive inhibitor of TSH binding. MAb 413.1.F7 did not affect hormone binding or response and was used as the control antibody for different experiments. Binding of MAbs was sensitive to the conformational changes caused by the activating and inactivating mutations and exhibited differential effects on hormone binding and response of these mutants. By studying the effects of these MAbs on truncation and chimeric mutants of thyroid stimulating hormone receptor (TSHR), this study confirms the tethered inverse agonistic role played by the hinge region and maps the interactions between TSHR hinge region [14] and exoloops responsible for maintenance of the receptor in its basal state. Mechanistic studies on the antibody-receptor interactions suggest that MAb 311.87 is an allosteric insurmountable antagonist and inhibits initiation of the hormone induced conformational changes in the hinge region, whereas MAb 311.62 acts as a partial agonist that recognizes a conformational epitope critical for coupling of hormone binding to receptor activation. Estimation of apparent affinities of the antibody to the receptor and the cooperativity factor suggests that epitope of MAb 311.87 (LRR 7-9) may act as a pivot involved in the initial events immediate to hormone binding at the LRRs. The anatgonsitic effect of MAB 311.62 on binding and response also suggested that binding of hormone is conformationally selective rather than an induced event. The hinge region, probably in close proximity with the α-subunit in the hormone-receptor complex, acts as a tunable switch between hormone binding and receptor activation. In contrast to the stimulatory nature of Cb-2 antibody such as MAb 311.62, MAb PD1.37, which identified residues aa 366–384 near Cb-3, was found to be inverse agonistic. Unlike other known inverse agonistic MAbs such as CS-17 [15] and 5C9 [16], MAb PD1.37 did not compete for TSH binding to TSHR, although it could inhibit hormone stimulated response. Moreover, unlike CS-17, MAb PD1.37 was able to decrease elevated basal cAMP of hinge region constitutively activated mutations only but not those in the extracellular loops. This is particularly important as interaction of hinge region residues with those of ECLs had been thought to be critical in maintenance of the basal level of receptor activation and are responsible for attenuating the constitutive basal activity of the mutant and wild-type receptors in the absence of the hormone. This was demonstrated by a marked increase in the basal constitutive activity of the receptor upon the complete removal of its extracellular domain, which returned to the wild-type levels upon reintroduction of the hinge region. However, careful comparison of the activities of the mutants (receptors harboring deletions and gain-of-function mutations) with maximally stimulated wild-type TSHR indicated that these mutations of the receptor resulted primarily in partial activation of the serpentine domain suggesting that only the ECD in complex with the hormone is the full agonist of the receptor. Confirmation of the above proposition has been difficult to verify primarily due to a highly transient conformational change in the tripartite interaction of the hinge region/hormone and the ECLs. The current approaches of using antibodies to probe the ECLs are difficult due to the conformational nature of the antigen as well as difficulty in obtaining a soluble protein. In chapter 5, the ligand induced conformational alterations in the hinge regions and inter-helical loops of LHR/FSHR/TSHR were mapped using the exoloop specific antibodies generated against a mini-Transmembrane domain (mini-TMD) protein. This mini-TMD protein, designed to mimic the native exoloop conformations, was created by joining the TSHR exoloops, constrained through the helical tethers and library derived linkers. The antibody against mini-TMD specifically recognized all three GpHRs and inhibited the basal and hormone stimulated cAMP production without affecting hormone binding. Interestingly, binding of the antibody to all three receptors was abolished by prior incubation of the receptors with the respective hormones suggesting that the exoloops are buried in the hormone-receptor complexes. The antibody also suppressed the high basal activities of gain-of-function mutations in the hinge regions, exoloops and TMDs such as those involved precocious puberty and thyroid toxic adenomas. Using the antibody and point/deletion/chimeric receptor mutants, dynamic changes in hinge region-exoloop interactions were mapped. The computational analysis suggests that mini-TMD antibodies act by conformationally locking the transmembrane helices by restraining the exoloops and juxta-membrane regions. This computational approach of generating synthetic TMDs bears promise in development of interesting antibodies with therapeutic potential, as well as, explains the role of exoloops during receptor activation. In conclusion (Chapter 6), the study provides a comprehensive outlook on the highly dynamic interaction of ligand and different subdomains of the TSHR (and to a certain extent of LHR and FSHR) and proposes a model of receptor activation where the receptor is in a dynamic equilibrium between the low affinities constrained state and the high affinity unconstrained state and bind to the hormone through the LRR 4-6. Upon binding the βL2 loop of the hormone contact LRR 8-10 that triggers a conformational change in the hinge region driving the α-subunit to contact the ECLs. Upon contact, the ECLs cooperatively causes helix movement in the TMH and ultimately in ICLs causing the inbuilt GTP-exchange function of a GPCR.